Exploring the historical perspective of the Ottomans Empire and North Africa - Eyesan, Orighmisan (Technium Social Sciences Journal, 2021)
Ottomans have a strong historical imprint on the African continent and its legacy has contributed to the sharping and rethinks of modern day historical history. Ottoman Empire histories can’t be emphasized without talking of the Balkan State, Byzantine Empire, Middle East, and Islam couple with Iran to North Africa. This article emphasizes the roots of both Ottomans and North Africa's historical context by providing a direct analysis of the janissaries who are the soldier loyal to the sultan (king) and the economic breakup of the Ottoman Empire, whereas that of North Africa starts with the 7th-century Arab conquests with Egypt, Muslim North Africa from 642, couple with the independence of the North Africa at 1951-1962. This article then went on to describe the 16th century Ottoman regency and piracy in North Africa, which is a time of struggle for dominance in the Mediterranean, and how Ottoman rule took over in North Africa, combined with the Ottoman administration of North Africa